The Association between Maternal Serum Vitamin D Levels and Gestational Diabetes Mellitus among Filipino Patients: A Cross-Sectional Study - Cabrera, Carmen Carina; Dampil, Oliver Allan; Ong-Lopez, Albert Macaire (Journal of the ASEAN Federation of Endocrine Societies, 2020)
,center> <center> </center><center>*Visual Abstracts prepared by Dr. Carmen Carina Cabrera</center> Objectives: To determine the association between low maternal serum vitamin D and gestational diabetes mellitus (GDM) among Filipino women in St. Luke’s Medical Center – Quezon City. Methodology: A cross-sectional study involving pregnant women at outpatient clinics in a tertiary hospital in the Philippines. Simultaneous testing for fasting blood sugar, 75g oral glucose tolerance test and serum vitamin D was done. Participants were classified as GDM versus non-GDM, and normal versus low serum vitamin D. Univariate and multivariate statistics were done to determine relationship between vitamin D and GDM. Results: Of 211 included women, 198 (93.8%) had low vitamin D levels, and 56 (26.5%) had GDM. Vitamin D was significantly higher in the GDM group (21.0±8.1 vs 18.8±5.3 ng/mL, p=0.0189). The proportion of women with low vitamin D levels was significantly higher among those without GDM (96.1% vs 87.5%, OR=0.28, p=0.029]. After adjusting for age, parity, history of GDM and pre-pregnancy BMI, no significant association was observed (adjusted OR=0.66, p=0.522). No correlation was seen between vitamin D and FBS (r=0.28, p=0.095), 1-hour post-75 g OGTT (r=0.26, p=0.643), and 2-hour post-75 g OGTT (r=0.28, p=0.113). Conclusion: There was an association found between maternal serum vitamin D level and GDM in the univariate analysis, but none was evident after adjusting for possible confounders. The unanticipated high prevalence of low vitamin D levels among pregnant Filipinos needs to be verified in future studies.